Validated quantitative trait loci for eggshell quality in experimental and commercial laying hens. (24th May 2018) - Tuiskula‐Haavisto, M.; Honkatukia, M.; Dunn, I. C.; Bain, M. M.; De Koning, D. J.; Preisinger, R.; Schmutz, M.; Arango, J.; Fischer, D.; Vilkki, J.
Summary: Compromised eggshell quality causes considerable economic losses for the egg industry. Breeding for improved eggshell quality has been very challenging. Eggshell quality is a trait that would greatly benefit from marker‐assisted selection, which would allow the selection of sires for their direct contribution to the trait and would also allow implementation of measurements integrating a number of shell parameters that are difficult to measure. In this study, we selected the most promising autosomal quantitative trait loci (QTL) affecting eggshell quality on chromosomes 2, 3, 6 and 14 from earlier experiments and we extended the F2 population to include 1599 F2 females. The study was repeated on two commercial populations: Lohmann Tierzucht Rhode Island Red line ( n  =   692 females) and a Hy‐Line White Plymouth Rock line ( n  =   290 progeny tested males). We analyzed the selected autosomal QTL regions on the three populations with SNP markers at 4–13 SNPs/Mb density. QTL for eggshell quality were replicated on all studied regions in the F2 population. New QTL were detected for eggshell color on chromosomes 3 and 6. Marker associations with eggshell quality traits were validated in the tested commercial lines on chromosomes 2, 3 and 6, thus paving the way for marker‐assisted selection for improved eggshell quality.